2005
DOI: 10.1002/yea.1239
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear actin‐related protein Act3p/Arp4p is involved in the dynamics of chromatin‐modulating complexes

Abstract: ## This work is dedicated to the memory of Dr Shigeki Mizuno, an outstanding scientist, an excellent teacher (to M.H., N.S. and Y.O.) and a dear friend (to U.W.). AbstractChromatin remodelling and histone-modifying complexes govern the modulation of chromatin structure. While components of these complexes are diverse, nuclear actinrelated proteins (Arps) have been repeatedly found in these complexes from yeast to mammals. In most cases, Arps are required for functioning of the complexes, but the molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 52 publications
4
39
0
Order By: Relevance
“…Nucleotide binding has been demonstrated directly for Arp1-Arp4 (5,(29)(30)(31)(32). We used a fluorescent ATP analog, 2′,3′-O-(2,4,6-trinitrophenylcyclo-hexadienylidene)-ATP (TNP-ATP), to explore the ability of yArp8 to bind nucleotides.…”
mentioning
confidence: 99%
“…Nucleotide binding has been demonstrated directly for Arp1-Arp4 (5,(29)(30)(31)(32). We used a fluorescent ATP analog, 2′,3′-O-(2,4,6-trinitrophenylcyclo-hexadienylidene)-ATP (TNP-ATP), to explore the ability of yArp8 to bind nucleotides.…”
mentioning
confidence: 99%
“…61 Gel-filtration analysis showed that only a proportion of Arp4 and Arp6 is found in the chromatin-remodeling complexes. 46,73,74 Consistently, yeast arp6Δ cells show a different pattern of gene expression to swr1Δ cells. 74 In addition, by genetic screenings, Arp5 and Arp6, but not Ino80 and Swr1, were identified as proteins involved in vacuolar protein sorting 75 and Arp5 was shown to be involved in nuclear architecture.…”
Section: Nuclear Arp Molecules Outside the Chromatin-remodeling Complmentioning
confidence: 74%
“…It has been shown that a portion of nuclear Arp4 occurs in a monomeric pool separate from the high molecular weight fraction that is usually associated with nuclear complexes. 29 Moreover, a role of Arp8 in chromosome alignment state are tricky and not well established. Furthermore, the roles of Arp4 and Arp8 in interacting with histones need to be separated from their potential roles in actin metabolism.…”
Section: Possible Roles For Actin-related Proteins Outside Of Their Hmentioning
confidence: 99%